1983
DOI: 10.1128/iai.40.2.675-683.1983
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a Shigella dysenteriae 1-like toxin produced by Escherichia coli

Abstract: A toxin from an enteropathogenic strain of Escherichia coli (E. coli H30) was purified to apparent homogeneity from cell lysates. The steps used to isolate the E. coli H30 toxin included French pressure-cell disruption of bacteria grown in iron-depleted media. Affi-Gel Blue chromatography, chromatofocusing, and anti-Shiga toxin affinity chromatography. The mobilities of the subunits of radioiodinated E. coli H30 toxin and Shiga toxin observed after the two toxins were subjected to sodium dodecyl sulfate-polyac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
95
2
2

Year Published

1985
1985
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(109 citation statements)
references
References 32 publications
9
95
2
2
Order By: Relevance
“…The reasons for this discrepancy are unclear. The value of 39 kDa would be consistent with a subunit composition of 1 A and 1 or more B subunits [2].…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The reasons for this discrepancy are unclear. The value of 39 kDa would be consistent with a subunit composition of 1 A and 1 or more B subunits [2].…”
Section: Discussionsupporting
confidence: 61%
“…The purification process described above was used to produce a VT preparation of high biologi-67 cal activity which, by gel filtration was 39 kDa in size; on SDS-PAGE analysis under reducing conditions, it contained a major protein with an estimated size of 32 kDa, and a polypeptide of less than 14 kDa which migrated with the buffer front. These correspond to the A and B subunits of the VT or Shiga-like toxin reported previously [2]. In that study, the A and B subunits were demonstrated using radiolabelled toxin, since sufficient material for visualization of unlabelled toxin by silver staining, as shown by the present study, was not available.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Verotoxins are E. coli cytotoxins which are lethal for cultured Vero cells (Konowalchuck et al, 1977). These toxins share a number of properties with Shiga toxin produced by Shigella dysenteriae and are therefore also called Shiga-like toxins (O'Brien and La Veck, 1983). Verotoxins consist of two groups, with VT1 (SLT-I) constituting one group and VT2 (SLT-II) and antigenically related toxins constituting a second group (Newland et al, 1988).…”
Section: Introductionmentioning
confidence: 99%